Phosducin-like protein PoPlp1 impacts cellulase and amylase expression and development in Penicillium oxalicum via the G protein–cAMP signaling pathway - Jia, Zhilei; Yan, Mengdi; Li, Xiaobei; Sun, Qiuyan; Xu, Gen; Li, Shuai; Chen, Wenchao; Shi, Zhimin; Li, Zhonghai; Chen, Mei; Bao, Xiaoming (Frontiers in Microbiology, 2023)
In this research, a phosducin-like protein, PoPlp1, was identified and functionally studiedinthe18 cellulase-producing strain Penicillium oxalicum 114-2. PoPlp1 was proven to participate inseveral19 biological processes, including mycelium development, conidiation, and expression of cellulasesand20 amylases. After the deletion of Poplp1, the morphology and development varied significantlyin21 ΔPoplp1. The colony growth, glucose utilization, and hydrolysis capability of starch andcellulose22 were limited, whereas the conidiation was enhanced. By detecting the expressionlevelsof23 transcription factors involved in asexual development, we conjured that PoPlp1 is involvedin24 conidiation by the major factor BrlA. We explored the effect of PoPlp1 on cellulase andamylase25 expression and observed that cellulase and amylase activities and major gene transcriptionlevels26 were all dramatically reduced in ΔPoplp1. The deletion of PoPlp1 caused a decrease in intracellular27 cAMP levels, and by external addition of cAMP, the cellulase gene expression level of ΔPoplp1was28 restored to a certain extent. These findings demonstrate that PoPlp1 may affect cellulase andamylase29 expressions by regulating cAMP concentration. To comprehensively explore the mechanismof30 PoPlp1 in regulating multiple biological processes, we performed comparative transcriptomic31 analysis between strains P. oxalicum 114-2 and ΔPoplp1. The major cellulase and amylasegenes32 were all down-regulated, coinciding with the results of real-time quantitative polymerasechain33 reaction. The genes involved in the G protein-cAMP signaling pathway, including several G-protein34 coupled receptors, one regulator of G protein signaling, and two cAMP phosphodiesterases, were35 disturbed by the deletion of PoPlp1. These results verified the positive function of PoPlp1intheGIn review 2This is a provisional file, not the final typeset article 36 protein-cAMP signaling pathway. The functional analysis of PoPlp1 is very beneficial for studying37 the regulatory mechanism of cellulase expression and other biological processes in P. oxalicum114-238 by the G protein-cAMP signaling pathway.